GE_GERICHTE P/14628/2021 vom 20. September 2024 - GE Cour de justice (2024)
TENTATIVE(DROIT PÉNAL);HOMICIDE;RIXE;LÉSION CORPORELLE SIMPLE;ENTRAVE À L'ACTION PÉNALE | CP.133.al2; CP.122; CP.111; CP.22.al1; CP.123; CP.305.al2